Artemis fowl: the arctic incident - Colfer, Eoin (Puffin Books London, 2003)
"Someone has been supplying Class A illegal human power sources to the goblins. Captain Holly Short of the LEPrecon Unit is sure that the person responsilbe is her arch-enemy, thirteen-year old Artemis Fowl. But is he?"--Back cover. Suggested level: intermediate, junior secondary